Treatment of corporate groups in insolvency under EU law - Sicignano, Luca (LUISS Guido Carli, 2017)
L’analisi svolta in questo lavoro ha ad oggetto le procedure adottabili in caso di fallimento, quando esse coinvolgono società costituite in gruppi di impresa. È una questione non recente che ha tuttavia avuto la sua consacrazione nel panorama internazionale solo negli ultimi anni. La grande crisi finanziaria del 2008 ha fatto sorgere la necessità di emanare nuove specifiche regole. Pertanto, l’obiettivo che questo lavoro si propone, è di analizzare tali regole, sia iure condito che iure condendo, per consentire al lettore di avere una panoramica chiara su come l’insolvenza di gruppo possa essere trattata.

A tranferência do risco no contrato de venda internacional de mercadorias em trânsito no âmbito da Convenção de Viena de 1980 - Damião, Ana Raquel Modesto (Universidade Nova de Lisboa, 2017)
International trade has had an increasing impact on the national economies of states. For this reason, some international institutions have sought to standardise rules on the international sale of goods. The Convention, which stands out from these rules, is the United Nations Convention on Contracts for the International Sale of Goods, opened for signature in Vienna on 11th April, 1980, known as the Vienna Convention (CISG). The transfer of risk is one of the most sensitive issues in international trade. Therefore, it would seem apt to observe the legal regime of the transfer of risk contained in the various provisions of this international instrument. To understand the rules of the transfer of risk, it is necessary to observe the notion of contract for the international sale and the obligations of the parties involved in the international contract. In addition, it should be noted that, in most situations, the contract for the international sale is related to the transport of goods. With this framework, the study of this essay focuses on the analysis of article 68 of the Vienna Convention. So, this dissertation deals with the question of determining the exact moment of the transfer of risk in the contract of international sale of goods in transit under the Vienna Convention. O comércio internacional tem tido cada vez mais impacto nas economias nacionais dos Estados. Por esse motivo, algumas organizações internacionais têm procurado uniformizar as regras relativas à compra e venda internacional de mercadorias. A Convenção, que se destaca dessas regras, é a Convenção das Nações Unidas sobre os Contratos de Compra e Venda Internacional de Mercadorias, aberta à assinatura em Viena a 11 de abril de 1980, conhecida como Convenção de Viena. A transferência do risco apresenta-se como uma das temáticas mais delicadas do comércio internacional. Portanto, afigura-se como útil a observação do regime jurídico da transferência do risco contido nas diversas disposições deste instrumento internacional. Para compreender as regras da transferência do risco, é necessário observar a noção de contrato de compra e venda internacional e as obrigações das partes do contrato internacional. Além disso, há que perceber que, na generalidade das situações, o contrato de compra e venda internacional está relacionado com o transporte de mercadorias. Com este enquadramento, o estudo deste trabalho centra-se na análise do artigo 68.º da Convenção de Viena. Assim, a presente dissertação debruça-se sobre a questão de determinar qual é o momento exato da transferência do risco no contrato de compra e venda internacional de mercadorias em trânsito no âmbito da Convenção de Viena.
Keywords: Convenção de Viena; Goods in transit; International sale; Mercadorias em trânsito; Transfer of risk; Transferência do risco; Venda internacional; Vienna Convention

L'équilibre contractuel - Muggeo, Marine-Alice (Université de Toulon, 2017)
Ces dernière années, le concept d'équilibre contractuel est devenu omniprésent dans notre droit et se retrouve dans quasiment toutes les disciplines du droit. L'équilibre contractuel n'a donc eu de cesse de se renforcer (Titre 1) dans diverses disciplines, car le droit des contrats est une matière transversale. On retrouve donc cette notion autant dans les contrats spéciaux que dans le droit commun des contrats. Ainsi une fois étudié, cet équilibre se retrouve dans les différentes phases de construction et d'exécution du contrat (Titre 2). C'est une partie qu'il faut appréhender car cela nous permet de comprendre où se retrouve l'équilibre dans le contrat. Et constater que c'est une notion centrale qui se retrouve dans l'ensemble des phases pré-contractuelles et contractuelles.
Keywords: Contrats d'affaires; Contrats informatiques; Contrats spéciaux; Crédit consommation; Droit des contrats; Honoraires avocats; Sécurité juridique

La Consolidation des comptes selon le SCF et les normes IAS/IFRS - Ayad, Bourbonienne; Kadid, Mohamed Redha (Ecole supérieure de Commerce, 2017)
Face à l’évolution des marchés économiques et financiers, les entreprises essayent de se développer, pour relever les défis contre la concurrence par la création des filiales et la fondation, pour créer des groupes commerciales et industrielles pour partager le risque et optimisé les dépenses fiscales. La consolidation des comptes est l'action d'établir des comptes uniques pour l'ensemble du groupe, afin de mieux en apprécier la réalité économique. Leur objectif majeur est de dépasser les limites des comptes individuels de chaque société pour refléter l'activité d'une société et de ses filiales. Dans notre mémoire on a consacré une partie théorique pour l’identification du périmètre et méthodes de consolidation ainsi que la présentation des différentes étapes principales composant le processus d’élaboration des comptes consolidés. Il serait utile de citer l’exemple de GEMA qui est un groupe Algérien, ce groupe établie la notion précédemment décrite, à travers laquelle a pu présenter des comptes et des états financiers consolidés. Ces états sont d’une telle conformité à la réglementation Algérienne généralement et aux SCF spécialement.

A sociedade unipessoal de direito angolano : contributo para a compreensão do seu regime jurídico - Salvador, Gorki (Universidade de Lisboa, 2017)
A presente investigação tem como objecto a Sociedade Unipessoal de Direito angolano. Com o desenvolvimento da mesma, ambicionamos prestar um contributo para a compreensão do regime jurídico positivo da unipessoalidade no Ordenamento Jurídico angolano. É um facto que o reconhecimento legislativo da Sociedade Unipessoal representa o acompanhamento, pelo Direito, da evolução da realidade económica, estabelecendo-se assim a necessária correspondência entre a realidade e o Direito. É do mesmo modo um facto que a Sociedade Unipessoal contraria a dogmática básica do Direito Societário, assente na ideia de que sociedade é uma realidade de que apenas uma pluralidade de indivíduos pode fazer recurso, ao ponto de se considerar a sociedade constituída por uma única pessoa uma autêntica contradictio in terminis. Portanto, o reconhecimento da unipessoalidade societária como uma situação ordinária, para além de acrescentar valores próprios ao ordenamento jurídico-societário, levanta uma série de questões que vão desde a contradição terminológica aos problemas concretos que apenas se levantam na presença da sociedade unipessoal ou que nelas se levantam com mais acuidade. A análise problemática de algumas perplexidades que se levantam no âmbito da Sociedade unipessoal ocupa as páginas do presente estudo.
Keywords: Angola; Direito das sociedades; Sociedade unipessoal

O exercício abusivo do direito de propriedade intelectual como infração à ordem econômica - Somensi, Ludmila (Universidade de São Paulo, 2017)
O presente trabalho busca analisar o exercício abusivo do direito de propriedade intelectual como infração à ordem econômica no direito brasileiro. A importância desse estudo se dá pela ausência de parâmetros e etapas de análise definidos para tais situações no Brasil, diferentemente do que ocorre em outros países, como Estados Unidos e os países membros da União Europeia, além da relevância da inovação para a sociedade e para o país. O caso brasileiro das autopeças, em curso perante o Conselho Administrativo de Defesa Econômica - Cade situa o estudo. A conclusão que se busca é a eleição de parâmetros e etapas que devem ser observados pela autoridade de concorrência brasileira na análise de um exercício abusivo de direito de propriedade intelectual como infração à ordem econômica e, especificamente, se tais parâmetros foram observados e investigados no caso das autopeças, considerando o exposto no último parecer opinativo do Cade. Para tanto, estuda-se a identificação de uma infração à ordem econômica e sua particularidade quanto a um direito de propriedade intelectual, tarefa bastante sensível, tendo em vista que é inerente ao direito de propriedade intelectual limitar a atuação de terceiros, enquanto o direito da concorrência evita a limitação à concorrência. Assim, verifica-se que esta exclusão de terceiros em relação ao objeto tutelado pelo direito de propriedade intelectual não significa uma limitação à livre iniciativa e, consequentemente, à livre concorrência, princípios visados pelo direito da concorrência, de tal forma que um direito de propriedade intelectual devidamente exercido não deve ser objeto de preocupação do direito da concorrência. Nesse sentido, estuda-se a função que determina a criação e o devido exercício de um direito de propriedade intelectual, para que seja verificado seu abuso, pressuposto da caracterização de uma infração ao direito da concorrência pelo exercício de um direito de propriedade intelectual. A decisão no caso europeu Microsoft auxilia este estudo tendo em vista que a autoridade de concorrência europeia elenca e comprova este e outros requisitos que devem ser investigados para a caracterização de uma infração à ordem econômica no direito brasileiro.
Keywords: Abuse of rights; Abuso do direito; Auto parts case; Competencia; Competition law; Concorrência desleal; Intellectual property; Microsoft case; Misuse violation to the economic order; Ordem econômica; Propriedade intelectual

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

Sociedade criada de facto e sociedade de facto no direito da OHADA : estudo comparativo jurisprudencial entre o direito brasileiro e português - Silva, Osvaldo Júlio da (Universidade de Lisboa, 2017)
A presente dissertação de Mestrado visa analisar e apresentar uma reflexão mais abrangente e aprofundada sobre a problemática inerente às sociedades criadas de facto e sociedades de facto no Direito da OHADA, nunca antes tratada pela doutrina nacional e (ou pela doutrina da OHADA) especializada, cujo resultado final esperamos poder contribuir, em certa medida, para o reforço da segurança jurídica e judiciária nos Estado-Membros da OHADA. As sociedades criadas de facto e sociedades de facto podem perturbar (e, efetivamente, perturbam) o exercício legítimo de atividades comerciais, uma vez que geram a insegurança jurídica e judiciária para investidores e para o comércio em geral. Com efeito, trata-se de realidades societárias, por vezes, constituídas e dissolvidas à margem do quadro legal vigente. À luz do artigo 98.º do Ato Uniforme Relativo as Sociedades Comerciais (AUS), todas as sociedades comerciais adquirem a personalidade jurídica a partir da sua matrícula no Registo do Comércio e do Crédito Mobiliário. Por isso, a maior parte da doutrina tem perdido demasiado tempo e energia na exegese deste preceito, deduzindo nele o efeito constitutivo do registo. Porém, temos para nós que a génese da sociedade reside na vontade das partes, tendo o registo o efeito principal de atribuição de um privilégio comercial de limitação da responsabilidade. Todavia, o registo não deixa de ser condicionante da plenitude da personalidade. A sociedade resulta de um contrato e não, necessariamente, do mero facto. This Master's thesis aims at analyzing and providing with a broadly and in-depth reflection on the problems connected to the partnership by estoppel and partnership de facto in OHADA Law, never before analyzed by national doctrine and (or OHADA doctrine). The final outcome of which we hope will contribute, at certain point, to the strengthening of legal and judicial certainty in the Member States of OHADA. Partnership de facto and partnership by estoppel may disturb (and, indeed, disrupt) the legitimate exercise of commercial activities, since they create legal and judicial uncertainty for investors and for trade in general. In fact, these corporate realities are sometimes constituted and dissolved out of the legal framework in force. Pursuant to the OHADA Uniform Act Relating to Commercial Companies and Economic Interest Group (UACC/EIG), registration is mandatory and companies only have legal personality as from the date of registration of the By-laws with the Registry of Companies. Thus, most of the doctrine has spent too much time and energy in the exegesis of this precept, deducing in it the constitutive effect of the register. As far as we are able to judge, the genesis of society lies in the will of the parties, and registration has the main effect of conferring a commercial privilege on limiting liability. However, it does not cease to be a condition of the fullness of personality. The company results from a contract and not necessarily from the mere fact.
Keywords: Direito comercial; OHADA; Sociedade comercial

Les sûretés négatives - Ndiaye, Paul Babou (Université Assane Seck de Ziguinchor, 2017)
Keywords: Clause d’inaliénabilité; Clauses de sûretés; Créances; Droits réels; Inexécution contractuelle; Negative pledge clauses; Sûreté négative; Sûretés

Le temps de la mode et la PI : protection des créations dans le domaine de l’habillement par les outils de la PI ou non sous le prisme de leur caractère éphémère et de leur propension à être copiées. - Machut, Gladys (Université Lille 2 Droit et Santé, 2017)
Keywords: Brevets d'invention; Contrefaçon; Droit; Intellectual property; Mode; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle

E-commerce et protection des données à caractère personnel : vers un renforcement de la protection des données à caractère personnel des consommateurs dans le cadre des opérations de e-commerce. - Maikuchel, Marine (Université Lille 2 Droit et Santé, 2017)
Keywords: Commerce électronique; E-commerce; Propriété industrielle; Protection de l'information (informatique); Protection des données

Reunião prévia no contexto do acordo de acionistas de controle - Abreu, Renata Silva Franco de (Instituto de Ensino e Pesquisa, 2017)
O presente estudo se propõe a analisar a reunião prévia, no contexto de acordo de acionistas de controle e voto em bloco, tendo em vista o direto societário atual, a fim de se verificar como este tema é tratado pela doutrina e como se reflete na prática das companhias brasileiras. Tomou-se por base a metodologia de abordagem descritiva e explicativa. Primeiramente, faz-se necessário discorrer sobre o acordo de acionistas, diferenciar o acordo de acionistas de controle e o acordo de acionistas de voto, bem como tratar sobre a legalidade destes acordos. Em seguida, analisa-se o instituto do voto em bloco, no contexto do acordo de controle; como o controle pode ser exercido por meio do voto em bloco; e os deveres decorrentes deste exercício de controle pelo bloco dos acionistas signatários de acordo de controle. Por fim, segue-se com a análise da reunião prévia, como meio para exercício de controle por meio do bloco decorrente do acordo de acionistas de controle. São tratados os principais temas relacionados à reunião prévia, quais sejam, formalidades deste órgão; como este órgão deve ser representado tendo em vista que não possui poder de representação propriamente dito; os temas sobre os quais as reuniões prévias não podem dispor; a importância na inovação da autotutela para tornar o acordo de acionistas mais efetivo; e a controvérsia acerca da vinculação da administração ao acordo de controle.

Risque de guerre - Barat, Louis (Aix-Marseille Université, 2017)

L'impact et les réponses d'un aéroport régional face à l'arrivée d'une ligne à grande vitesse - Benzoubair, Yannis (Aix-Marseille Université, 2017)

L'anticipation des conflits sociaux chez le transporteur ferroviaire de passagers - Boutaleb, Lylia (Aix-Marseille Université, 2017)

Les NTIC dans le parcours passager : Quel futur pour l'expérience client en aéroport ? - Brillaud, Alexandre (Aix-Marseille Université, 2017)

La protección jurídica de las invenciones en materia de biotecnología a través del régimen de patentes - Bueno González, Antonio (Universidad Internacional de Andalucía, 2017)
Trabajo Fin de Máster en Biotecnología Avanzada. Director/Tutor: Eugenio Olmedo Peralta. En este trabajo, tras analizar la normativa vigente en materia de propiedad industrial, así como su evolución histórica, se han expuesto los principales aspectos de la regulación actual de las creaciones biotecnológicas. Éstas poseen ciertas singularidades respecto a las invenciones convencionales al estar constituidas total o parcialmente por materia biológica, lo que les hace requerir de un régimen de protección especial, o al menos el realizar ciertas adaptaciones respecto de la normativa básica de patentes, puesto que ésta se creó en su origen considerando invenciones de carácter eminentemente técnico surgidas en la revolución industrial. Esta tarea se ha llevado a cabo con el objetivo de considerar las posibles soluciones existentes para solventar las carencias de la normativa y ofrecer una protección adecuada a las invenciones biotecnológicas, tal que proporcione una justa remuneración al inventor, fomentando a su vez el desarrollo tecnológico. También se han expuesto las principales características del régimen de las obtenciones vegetales, creado para dar protección a las variedades vegetales desarrolladas. De esta manera, se han abarcado la mayoría de los supuestos de protección legal de creaciones de base biológica, ya sean invenciones patentables o variedades vegetales, profundizando más en las primeras. Así, tras realizar una revisión bibliográfica de las principales aportaciones realizadas en la materia y de la legislación al respecto, contemplando las principales dificultades y singularidades que las creaciones basadas en materia viva presentan en cuanto a su protección jurídica, se puede afirmar que, hoy por hoy, el método de protección mediante patentes es el más adecuado para las invenciones biotecnológicas. Ello es debido a la gran experiencia acumulada que se tiene con este sistema, el cual se ha ido adaptando a este tipo de invenciones a lo largo de los años, siendo el que mejor recompensa proporciona al inventor y el que posee una mayor importancia económica, actuando como un agente dinamizador e impulsor del desarrollo tecnológico. Pese a esto, no se puede ignorar la necesidad de ir adaptando día a día la legislación a la vanguardia de la técnica, intentando proporcionar soluciones equitativas para la sociedad en general, respetando los derechos humanos y ciertos principios éticos, y a su vez intentando fomentar el desarrollo tecnológico, en áreas como la biotecnología, tan necesario para solventar numerosos problemas de nuestra sociedad contemporánea.
Keywords: Brevet; Intellectual property; Propriedad industrial; Propriedad intelectual; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle

La mise en place d'un cadre coercitif face aux passagers indisciplinés - Camus, Agathe (Aix-Marseille Université, 2017)

Aviation d'affaires : Business models innovants et conséquences sur le marché - Cano, Olivier (Aix-Marseille Université, 2017)

Les enjeux de la réglementation sociale applicable au secteur ferroviaire - Catherin, Cécile (Aix-Marseille Université, 2017)

La acción social de responsabilidad - Cerezuela Moraleja, Alejandro (Universidad Internacional de Andalucía, 2017)
Trabajo Fin de Curso de Experto Universitario en Derecho Societario (2016/17). Tutora: Dra. Patricia Márquez Lobillo. Ante la conducta por la que el administrador social causa un daño al patrimonio de la sociedad, la Ley de Sociedades de Capital ofrece un mecanismo por el cual poder exigirle la reparación del daño, mediante la acción social de responsabilidad, que podrá ser ejercida por la sociedad, los socios o terceros, con la finalidad de restablecer el patrimonio social. Este trabajo nace con la intención de ofrecer un enfoque práctico para el ejercicio de la acción, estudiando los elementos necesarios que han de cumplirse en cada uno de los legitimados para poder ejercitarla eficazmente y cómo actuar frente a la acción por quien no esté de acuerdo a su ejercicio. Para todo ello se apoya el trabajo en la jurisprudencia más actual y relevante en cada supuesto.

Les « navires autonomes ». Enjeux et impacts d'une navigation sans équipage dans le monde maritime - Chesneau, Anaïs (Aix-Marseille Université, 2017)
Les navires sans équipage sont une innovation dans l’industrie du transport maritime. Technologiquement viables, ils sont en passe de révolutionner le secteur en promettant une rentabilité accrue, et un impact environnemental moindre. Certaines incertitudes persistent cependant. D’une part, le droit maritime international n’est pas adapté à leur exploitation et nécessite d’être modifié ; d’autre part, leur fiabilité n’est pas démontrée, et les assureurs restent en position d’attente face à l’incertitude des risques et la question de la navigabilité des navires sans équipage.
Keywords: Droit maritime; Navigation; Navigation sans équipage; Navire autonome; Navire intelligent; Équipage

L'impact des sociétés de réclamation sur l'indemnisation des passagers en cas d'irrégularité d'exploitation - Cotoni, Lou (Aix-Marseille Université, 2017)

La livraison : étude de droit comparé entre transport maritime et routier - Couturier, Loic (Aix-Marseille Université, 2017)

La saisie de soutes - Dagonneau, Catherine (Aix-Marseille Université, 2017)
La saisie de soutes est une figure originale du droit maritime. En tant qu’ « élément du navire », les soutes sont susceptibles de faire l’objet d’une saisie indépendamment du navire. Elles constituent ainsi un gage pour les créanciers dénués de « créance maritime » ou de privilège maritime. En période d’instabilité économique, la saisie de soutes est indispensable à la confiance des fournisseurs de navires. Cependant, depuis l’arrêt Saint Pierre de 1998 et l’analyse qui en a été faite par les auteurs, la saisie conservatoire de soutes a quasiment disparu des prétoires. Elle a aujourd'hui vocation à être remplacée par la saisie-revendication, instrument de recouvrement efficace même en cas de faillite du débiteur.
Keywords: Alternative à la saisie de navire; Moyen de pression; Saisie conservatoire; Saisie de soutes; Saisie revendicative

La menace du modèle commercial low-cost long-courrier de Norwegian Airlines pour les compagnies majors européennes - Dahel, Jessim (Aix-Marseille Université, 2017)

Etude sur les correspondants de clubs de protection - Dalmas, Julien (Aix-Marseille Université, 2017)

An investigation into the relationship between the UNIDROIT Principles of International Commercial Contracts (UPICC) and the UN Convention on the International Sale of Goods (CISG) - Daniel, Jason (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: Commercial law; Conflict of laws; Contracts (International law); International Institute for the Unification of Private Law; UNIDROIT principles of international commercial contracts 2010; United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

La lettre de garantie chez un courtier en assurances maritimes - Delaubier, Clara (Aix-Marseille Université, 2017)
La lettre de garantie P&I est un instrument né de la pratique, qui permet de sécuriser une créance maritime, tout en permettant aux transactions commerciales sous-jacentes au voyage maritime, de perdurer. Sa force réside dans le fait qu’elle fasse converger des intérêts pourtant opposés, à savoir les intérêts cargaison d’une part et les intérêts corps d’autre part, en répondant aux exigences de rapidité et de fluidité qu’impose le commerce maritime mondial. Sa négociation, au même titre que son exécution, impliqueront l’intervention d’une multitude d’acteurs, qui défendront donc des intérêts variés mais qui auront tous comme objectif de résoudre leur litige par la voie amiable. La lettre de garantie, en tant qu’instrument du commerce maritime, reflète également les rapports de force existant entre les intérêts en jeux et permet de mettre en lumière la bataille de compétences, opposant principalement l’Angleterre à la France. Cette étude a donc pour but d’analyser les différentes implications légales et pratiques de ce formidable instrument.
Keywords: Action directe; Compétence; Correspondant P&I; Courtier en assurances maritimes; Créance maritime; Lettre de garantie P&I; Responsabilité du transporteur; Transport maritime

Abordage maritime et fluvial : responsabilité et traitement assurantiel - Fallot, Victoire (Aix-Marseille Université, 2017)

Etude sur la réduction de la sinistralité en matière de transport routier de marchandises - Fassy, Florian (Aix-Marseille Université, 2017)

Análisis de los contratos de leasing, renting y factoring - Gallardo Rial, José Luis (Universidad Internacional de Andalucía, 2017)
Trabajo Fin de Curso de Experto Universitario en Derecho Bancario (2015/16). Directora/Tutora: Dra. Dª María Belén González Fernández. El presente trabajo tiene por objeto el estudio, análisis y conocimiento de tres de los diferentes tipos de contratos de arrendamiento financiero existentes y más usados en la actualidad: Leasing, renting y factoring. Se ha analizado de manera independiente y pormenorizada cada uno de ellos, individualizando sus características y funcionamiento a efectos de diferenciarlos y clasificarlos para concretar los casos en los que resultan de utilidad.
Keywords: Affacturage; Crédit-bail

Accident de Germanwings Symptomatologie d'un métier en évolution et intégration des risques - Gavriil, Lydia (Aix-Marseille Université, 2017)

Special and differential treatment provisions within the World Trade Organization : the pursuit of development for developing countries - Hiine, Karabo (University of KwaZulu-Natal, 2017)
Abstract not available.
Keywords: Differential Treatment Provisions; Multilateral system; Special Treatment Provisions; Trade liberalization; WTO; World Trade Organization

La faute nautique - Jebrayel, Anthony (Aix-Marseille Université, 2017)
La faute nautique est l’acte ou négligence du capitaine, marin, pilote, ou préposé du transporteur de marchandises dans la navigation ou dans l’administration du navire. Il s’agit d’un cas excepté, c’est-à-dire qu’elle est de nature à exonérer le transporteur de la responsabilité afférente aux pertes ou dommages à la marchandise, vis-à-vis de l’ayant-droits : chargeur, destinataire ou assureur subrogé. Le présent mémoire s’attache à faire le constat suivant : autour du globe, l’approche qui en est faite par le droit – ensembles législation, doctrine, et jurisprudence – est très étroite. Aussi bien le domaine que les effets de l’exonération pour faute nautique sont ainsi restreints ; les deux étant amoindris par la preuve d’un manquement du transporteur maritime - la faute dans les soins devant être apportés à la cargaison, ou la faute dans la mise en état de navigabilité du navire. L’abordage à faute commune ainsi que l’institution de l’avarie commune peuvent néanmoins générer des situations où l’on constate que la faute nautique joue pleinement. Si l’évolution actuelle du droit maritime semble devoir écarter la faute nautique, comme l’en atteste l’adoption récente des Règles de Hambourg, puis des Règles de Rotterdam, il reste que le cas excepté peut aujourd’hui être invoqué dans la plupart des transports, étant donné la large application de la Convention de Bruxelles du 25 août 1924. Aussi, cette spécificité de la matière maritime mérite certainement une plus grande considération, et l’auteur plaide en ce sens pour une approche moderne et plus cohérente de l’exonération pour faute nautique.
Keywords: Avaries communes; Cas exceptés; Connaissement; Droit maritime; Faute nautique; Responsabilité; Règles de La Haye; Règles de La Haye-Visby; Transporteur maritime

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

Recognition and enforcement of foreign judgments : proposals for OHADA - Kazadi, Nshingu (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract

La diversité des aires marines protégées françaises - Lavigne, Nicolas (Aix-Marseille Université, 2017)

L'ubérisation du transport de dernier kilomètre le phénomène appliqué à l'activité de coursier à vélo - Lemire, Charlotte (Aix-Marseille Université, 2017)

Les effets de l'affretement aérien dans le dévoloppement économique des régions - Marziali, Nicolas (Aix-Marseille Université, 2017)

A critical analysis of the fiduciary duties of directors and evaluation of the development of these duties in terms of the common law and statutory law - Mdunge, Mzwendoda Smiso Patson (University of KwaZulu-Natal, 2017)
Corporate law is based on the premise that directors are fiduciaries of their companies. This is an unbending duty which has to be adhered to at all cost by individuals appointed as directors of a company. Previously the director’s duties were governed by the common law which often relied on the interpretation of the courts on a case by case basis. Therefore the courts would often arrive at different conclusions based on a similar set of facts. The advent of the 2008 Companies Act (Act 71 of 2008)1 brought about a major evolution in South African company law by partially codifying the fiduciary duties of the directors. Understanding fiduciary duties of a director is of significant importance in the modern democracy based on the fact that directors engage on the international spectrum. Company directors have discretionary power which may be abused if they are not familiar with the fiduciary duties. This study seeks to comprehend fully the fiduciary duties of a director of a company. These are the duty to act bona fide, the duty to act for a proper purpose, the duty to avoid conflicts of interest and the duty not to use a corporate opportunity and information for personal profit. This task will be undertaken both in terms of the common law as well as statute (Companies Act 2008 Act). The study will delineate the fundamental consequences of partial codification of these duties and set out the current legal position of the common law which operates in tandem with the statute. In addition, it will deal with whether the common law provisions are still applicable side by side with the statutes. The duties of a company director represent a subject that is not merely academic in nature, but one that is of vital importance in our ever changing commercial world. More and more people are appointed as company directors every day and often they do not know or understand the implications of what they have agreed to.
Keywords: Common law; Companies Act 71 of 2008; Corporate law; Duties of directors; Duty to act in good faith; Fiduciary duties

La navigation maritime dans l'Arctique russe - Mukhina, Anastassiya (Aix-Marseille Université, 2017)

Contractual regulation : infusing the law of contract with constitutional values - Ndlebe, Zithulele Fikile (University of Johannesburg, 2017)
The Constitution of the Republic of South Africa is the supreme law in the land. Thus, all law is subject to the Constitution and this inevitably includes the law of contract. The South African law of contract has been inherited from common law, namely Roman–Dutch law and has been applicable in South Africa to date. The Constitution states that the common law should be developed when it is not in line with the provisions of the Constitution. The values underpinning the Constitution are human dignity equality and freedom and these values must therefore be reflected in contractual relations. The common law principle of pacta sunt servanda, which means that agreements must be kept, at times this principle yields unjust and unreasonable results. The strict adherence to pacta sunt servanda has led to difficulties. The unenforceability of these contract terms has been shown in reported case law to stem from standard term contracts, unequal bargaining power and from persons who contract out of necessity. This dissertation concludes that South African law of contract and the current legal treatment of balancing contract law with constitutional values is unsatisfactory. The Bill on the Control of Unreasonableness, Unconscionableness, or Oppressiveness in Contracts or Terms which was tabled in 1998 should be revised and legislated, so as to regulate contracts and infuse the law of contract with the constitutional values of human dignity, equality and freedom.

Les mécanismes de financement de l'économie sociale et solidaire en Afrique Subsaharienne Application au Congo-Brazzaville et au Sénégal - Ngouala Mongo, Belda; Thiao, Marie Hélène (Université Mouloud Mammeri, 2017)
L’Economie Sociale et Solidaire (ESS) est une nouvelle économie née des inégalités qu’ont connues les sociétés prolétaires mais qui de nos jours demeure une alternative pour lutter contre les conséquences désastreuses de l’économie capitalistique et de la mondialisation. Son principe de base étant de placer l’Homme au cœur de ses diverses activités et organisations, lui permet ainsi de promouvoir la solidarité, une gestion participative, etc. Cependant, elle doit faire face à des problèmes et surtout de financement. C’est dans ce contexte que nous nous interrogeons sur une question de grande actualité aussi en Afrique Sub-saharienne (AfSS) et particulièrement au Congo Brazzaville et au Sénégal à savoir : les mécanismes de financement de l’économie social et solidaire. L’objectif pour nous, est d’étudier les éléments qui forment, cadrent et financent l’ESS en AfSS et particulièrement au Congo-Brazzaville et au Sénégal et de vérifier si les dispositifs existants répondent-ils aux valeurs et principes de l’ESS t-elle que connu aujourd’hui dans le monde. De ce fait, et à partir de nos recherches, nous orientons notre travail sur : le Cadre théorique de cette ESS et ses pratiques en AfSS ; son cadre juridique et dynamique et enfin son rôle et système de financement dans l’activité économique au Congo-Brazzaville et au Sénégal. Ce qui nous a permis d’ailleurs de comprendre que l’ESS est un concept ancien dont les valeurs et pratiques ont toujours existés en AfSS. Qu’elle repose sur des dispositifs juridiques et des réseaux de promotion. Et que malgré quelques insuffisances notoires, les dispositifs financiers mis en place dans ces deux pays en particulier ont permis le développement et la modernisation des pratiques et organisations de l’ESS

A responsabilidade social corporativa face aos danos ambientais sob a perspectiva do direito internacional - Nunes, Bárbara Nogueira (Universidade Federal Fluminense, 2017)
A governança global é um fenômeno relativamente novo na ordem internacional. A responsabilidade social corporativa surge como um mecanismo da governança global no que tange à responsabilização das sociedades que assumem atribuição cada vez mais relevante diante do mundo globalizado. Os danos ambientais comumente são fruto da ausência de instrumentos efetivos de responsabilidade. O descarte de resíduos sólidos nos oceanos há tempos vem acontecendo e prejudica o meio ambiente marinho vinculado às águas brasileiras. A comunidade internacional enfrenta o descarte de resíduos em águas internacionais basicamente por meio da elaboração de uma legislação que objetiva regulamentar o despejo de resíduos nos oceanos. Assim, cabe investigar se há uma efetiva resposta ao enfrentamento do problema em termos da logística jurídica atualmente utilizada e sua fiscalização pela comunidade internacional. Parte-se da hipótese de que os instrumentos legais em vigor não se apresentam como uma solução estanque ao problema ante a argumentação da soberania dos Estados que leva a não observância das normas internacionais e a não responsabilização dos infratores. Um mecanismo mais eficaz em termos de regulamentação e de fiscalização, aliado à conscientização e educação ambiental são exigências que se fazem necessárias para combater os efeitos dessa prática que ecoa um dano permanente ao meio ambiente marinho. A metodologia utilizada neste trabalho dar-se-á através da análise teórica sobre o fenômeno a partir de doutrina selecionada que trata das construções conceituais que abordam o tema.
Keywords: Challenges; Comunidade internacional; Corporate Social Responsibility; Dano ambiental; Desafios; Descarte de resíduos; Gerenciamento de resíduo; Global governance; Governança global; Internation; Ocean dumping; Poluição ambiental por resíduo industrial; Responsabilidade social corporativa; Responsabilidade social da empresa; Solid environmental damage; Sólidos danos ambientais; Waste disposal

The impact of leadership styles on organizational performance - Nzimande, Sandile Jerome (University of KwaZulu-Natal, 2017)
Many contemporary private and public enterprises have been hit by scandals and underperformance which have been linked to organizational leadership. This study therefore sought to establish the impact of leadership styles on organizational performance. Leadership and organizational performance crises that have rocked institutions such as Eskom, the South African Broadcasting Corporation and the South African Airways, Steinhoff, Enron and others necessitated the study. The study focused on MBA year three students (class of 2017) at the University of KwaZulu-Natal. The assumption has been that since these are masters’ students, they have once been exposed to various leadership styles, some of them are leaders, all have studied leadership styles and therefore likely to understand how these styles impact on organizational performance. This is a quantitative study. The total population was 140 students of which a total of 100 were targeted. Simple random sampling was used. Most of the participants revealed that there is a significant link between leadership styles and organizational performance. They unanimously agreed that there is definitely a noteworthy relationship between leadership styles and the organizational performance. The respondents also revealed that transformational leadership style is the most complimentary leadership style to organizational performance followed by strategic and open leadership styles respectively. Participants agreed that toxic leadership style and autocratic leadership style are undermining the organizational performance. It is therefore recommended that organizations ensure continuous checks on leadership in order to ensure that available leadership can assist in the realization of organizational goals. In addition, it is also recommended for organizations to assess the "type" of a leader in terms of leadership styles before he/she is promoted to take leadership roles in the organization in order to make proper placements. This will allow the organization to assess whether that type of a leader is suitable for the organization. Future research is needed on how models can be developed on how to make proper placements to leadership levels/roles. Research should also focus on how leadership styles dovetail with other organizational efforts that are meant to boost organizational performance.
Keywords: Leadership styles; Organizational performance; Private enterprises; Public enterprises

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.

Enjeu social et activité aéroprtuaire, du risque à l'opportunité - Sarr, Adama (Aix-Marseille Université, 2017)

The compatability of the restatement second of the conflict of laws and South African private international law with Article 2(2) of the Hague Principles on Choice of Law in International Commercial Contracts - Seckel, Ashely Zwelinhle (University of Johannesburg, 2017)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Le contrat de charter des navires de grande plaisance - Thierry, Jean-Baptiste (Aix-Marseille Université, 2017)
L’affrètement est un élément incontournable du droit maritime. L’outil que représente le contrat d’affrètement, bien que légalement encadrée, a été notamment forgé et standardisé par les professionnels qui ont su tirer pleinement profit de la liberté contractuelle qu’offrait ce mode d’exploitation. C’est grâce à cette liberté accordé aux parties que l’affrètement a été choisi pour exploiter les navires de grande plaisance. Cependant, malgré que le régime d’affrètement soit adapté à ce type de navigation, la prestation découlant de la mise à disposition d’un yacht doit faire face à de nombreux enjeux fiscaux, juridiques et sociaux qui obligent l’industrie si particulière du yachting à réagir en conséquence et se tourner vers d’autres mode d’exploitation tel que le contrat de croisière.
Keywords: Contrat de charter; Grande plaisance; Navire; Navire de grande plaisance